UPAYA PEMBERDAYAAN MASYARAKAT PEDULI STROKE DENGAN PELATIHAN DETEKSI DINI STROKE - Awan, Awan Hariyanto (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Stroke or Cerebral Vascular Disease (CVD) is a disease that often causes death and disability, both in urban and rural areas. The impact of a stroke includes paralysis of the limbs, impaired vision, difficulty speaking and swallowing, and psychological impacts such as frustration and irritability. Stroke can also cause neurological deficits that have an impact on the patient's quality of life. Data from World Health Organization (WHO) shows that 75.6% of elderly people who experience stroke require home care, which has a positive impact on patient recovery. In Trenggalek Regency, the incidence of stroke reached 3,771 people in 2019. Early proper handling can improve the patient's condition, and the community needs to be educated to recognize stroke symptoms. In order to increase public awareness and knowledge about early detection of stroke, this Community Service activity aims to train community cadres in detecting stroke symptoms early. The method used is Focus Group Discussion (FGD) and training for community cadres who care about stroke, this method is very effective in increasing the knowledge and skills of cadre participants about early detection of stroke after receiving training materials, the cadre's knowledge and skills increased significantly, from 5 cadres (42%) who were initially in the good category and 7 cadres (58%) in the sufficient category, to all or 12 cadres (100%) whose knowledge and skills increased in the good category. This community empowerment can change the attitudes and behavior of participants from not knowing to knowing, from knowing to wanting, and finally being able to carry out early detection of stroke and can be disseminated to the community. This activity will contribute to improving the health and quality of life of the Trenggalek community.